The influence of religious identification on strategic green marketing orientation - Casidy, Riza (Journal of business ethics, 2024)
Small and medium-sized enterprises (SMEs) play a critical role in the green economy due to their significant environmental footprint. Because more than 84% of the world’s population identifies with a religion, most SME top-executives are likely to identify with a religion that would influence their decision-making. Despite these recent advances, prior studies have focused on SMEs’ external drivers and did not consider the role of internal drivers, such as the characteristics of SMEs’ top-executives, in influencing green marketing strategy. We aim to address this gap by focusing on religious identification as a key driver of green marketing by SMEs. Specifically, we examine the effects of top-executives’ religious identification on strategic green marketing orientation (SGMO), and how such effects are moderated by political ideology. Using respondents comprised of CEO and/or owner-managers of SMEs in the US, the results show empirical evidence supporting the importance of religious identification in influencing green marketing decisions. Moreover, we found that the effects of religious identification on SGMO are more pronounced among top-executives with Conservative ideology.